The tricontinental revolution : Third World radicalism and the Cold War - Parrott, R. Joseph, 1985-; Lawrence, Mark Atwood (Cambridge : Cambridge University Press, 2022)
The Tricontinental Revolution provides a major reassessment of the global rise and impact of Tricontinentalism, the militant strand of Third World solidarity that defined the 1960s and 1970s as decades of rebellion. Cold War interventions highlighted the limits of decolonization, prompting a generation of global South radicals to adopt expansive visions of self-determination. Long associated with Cuba, this anti-imperial worldview stretched far beyond the Caribbean to unite international revolutions around programs of socialism, armed revolt, economic sovereignty, and confrontational diplomacy. Linking independent nations with non-state movements from North Vietnam through South Africa to New York City, Tricontinentalism encouraged marginalized groups to mount radical challenges to the United States and the inequitable Euro-centric international system. Through eleven expert essays, this volume recenters global political debates on the priorities and ideologies of the Global South, providing a new framework, chronology, and tentative vocabulary for understanding the evolution of anti-imperial and decolonial politics.
Title from publisher's bibliographic system (viewed on 10 Jan 2022).
Keywords: Decolonization -- Developing countries -- History -- 20th century; Revolutions -- Developing countries -- History -- 20th century; Cold War; Developing countries -- Foreign relations -- 20th century; Developing countries -- Foreign relations -- United States; United States -- Foreign relations -- Developing countries